Unmarried University Students’ Perspectives on Women’s Ideal Age at First Birth: Evidence from Bangladesh (International Journal of Statistical Sciences, 2026)
Understanding university students’ perceptions of women’s ideal age at first birth (WIAFB) is essential for informing future reproductive health policies and programs in a given country. This study aimed to survey Bangladeshi university students’ perspectives on WIAFB. A cross-sectional study was conducted at University of Rajshahi, Bangladesh and 466 unmarried students were recruited through multistage stratified random sampling. Students’ perspectives on WIAFB were measured using a question: “At what age do you think women should ideally have their first child?” Based on their responses, students were categorized into two groups: (i) early age at childbirth (